Diabetes mellitus do tipo I em cão (canis lupus familiaris) - relato de caso - Martins, Lorena Nogueira (Universidade Federal Rural do Semi-Árido, 2017)
This report describes the activities carried out during the mandatory supervised internship at the Dix-Huit Rosado Maia Veterinary Hospital of the Federal Rural Semi-Arid University, Campus Mossoró / RN, from June 26, 2017 to October 6, 2017, totaling 240 hours. Aiming to improve the knowledge acquired during the course of veterinary medicine and correlating with practical activities in the area of medical practice of small animals, we sought to describe the clinical case of a dog (Canis lupus familiaris) with diabetes mellitus. Of all the cases followed during the stage, the case of a 9-year-old poodle dog stood out. It arrived at the hospital showing signs of polyuria, polydipsia, polyphagia and cataract. The animal was diagnosed with diabetes mellitus through the clinical signs presented and the results of the examinations, then it was prescribed the correct treatment for the pathology obtaining a significant regression of the clinical signs and consequently the improvement in the quality of life of this animal.
Relatório
Keywords: Cão; Diabetes; Endocrinologia; Dog; Diabetes; Endocrinology; CIENCIAS AGRARIAS::MEDICINA VETERINARIA